Digitalising the curriculum : teachers’ integration of technological resources into the CAPS framework - Nene, Lindokuhle Gary; Sokhulu, Lerato Hlengiwe (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
The rapid development of technological resources has propelled various sectors to adopt digitalised practices. Similarly, the integration of technological resources at the basic education level was rendered inevitable, particularly during the Coronavirus pandemic era and beyond. These technological developments affect curriculum implementation in schools and enhance teaching and learning practices. This qualitative case study explored teachers’ integration of technological resources into the curriculum in the Fourth Industrial Revolution era in South African primary schools. The interpretive paradigm was used to provide insights into teachers’ integration of technological resources. Three teachers were purposively and conveniently sampled to participate in the study. Data were generated using online one on-one semi-structured interviews and Zoom Focus Group Discussions. Technological Pedagogical Content Knowledge (TPACK) served as an analytical tool to frame the study. Findings indicate that teachers primarily rely on personal knowledge (personal integration) and social influences (informal integration) when integrating technological resources, rather than on the Department of Basic Education's formal policy guidelines (formal integration). While informal integration is influenced by teachers' technological knowledge and skills gained through social networks, personal integration of technological resources is shaped by each teacher's individual opinions and available opportunities. Conversely, formal integration conforms to institutional policies and structured curriculum requirements. This study recommends that teachers give formal integration of these resources utmost priority because of the ongoing structural limitations, including inadequate professional development, limited infrastructure, and the demands of a curriculum that is content-heavy
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 9, 2025
Keywords: Integration; Technological resources; Curriculum; Teachers; Integration (Theory of knowledge); Curriculum change; Curriculum planning; Education -- Curricula; Electronic data processing; Teaching -- South Africa; Basic education -- South Afica